2021
DOI: 10.2215/cjn.11020720
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Deprivation, Geographic Location, and Access to Pediatric Kidney Care in the United Kingdom

Abstract: Background and objectivesPre-emptive kidney transplantation is advocated as best practice for children with kidney failure who are transplant eligible; however, it is limited by late presentation. We aimed to determine whether socioeconomic deprivation and/or geographic location (distance to the center and rural/urban residence) are associated with late presentation, and to what degree these factors could explain differences in accessing pre-emptive transplantation.Design, setting, participants, & measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 40 publications
1
34
0
1
Order By: Relevance
“…While no association was found in Australia (contrary to remoteness) 21 , a study found such disparities in the UK for access to pre-emptive kidney transplantation but not for late referral. 12 In the US, a better access to pre-emptive transplantation was found for white children. 9,22 Regarding modality of dialysis initiation, Schaefer et al found that the use of nightly intermittent PD at a country level increased with growth national income contrary to continuous ambulatory PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While no association was found in Australia (contrary to remoteness) 21 , a study found such disparities in the UK for access to pre-emptive kidney transplantation but not for late referral. 12 In the US, a better access to pre-emptive transplantation was found for white children. 9,22 Regarding modality of dialysis initiation, Schaefer et al found that the use of nightly intermittent PD at a country level increased with growth national income contrary to continuous ambulatory PD.…”
Section: Discussionmentioning
confidence: 99%
“…These results raise questions about the barriers leading to social inequality since pre-emptive kidney transplantation has been shown to improve kidney transplant outcomes. 36 Plumb et al recently showed in the UK that the association between social deprivation and access to pediatric kidney care could be mediated by the access to living donor transplant, 12 but the reasons explaining this social gradient are certainly more complex (psychosocial decision, role of clinicians' perspective…) and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of CJASN, Plumb et al (1) published their analysis of the associations between deprivation, geographic location, and access to pediatric kidney care in the United Kingdom. Over a 20-year period, they examined a cohort of children who started KRT between the ages of 3 months and 16 years of age.…”
mentioning
confidence: 99%